Eternal Gandhi Multimedia Museum (2005)
[Dt.:] Die multimediale Ausstellung "Eternal Gandhi" ist ein Projekt der Stiftung Sacred World Foundation, die in den Räumen der Smriti and Darshan Samiti in New Delhi gezeigt wird. Die musealen Installationen, die unter Einsatz modernster Hochtechnologien umgesetzt wurden, spiegeln und interpretieren Gandhis Leben und Werk und (über-)führen seine Ideen in das multimediale Zeitalter. Die Homepage zur Ausstellung informiert nicht nur über die Bedeutung und Hintergründe der einzelnen Ausstellungsstücke, sondern ermöglicht auch via Videosequenzen Einblicke in die Räumlichkeiten oder in die Eröffnungszeremonie. - [Engl.:] This exhibition on Mahatma Gandhi, shown at Gandhi Smriti and Darshan Samiti in New Delhi, is realised by the think tank Sacred World Foundation, whose projects are exploring innovation created by building bridges between techno and traditional cultures. The Eternal Gandhi Multimedia Museum is one of the world's first digital multimedia museums. It is located at the site where Mahatma Gandhi attained martyrdom. The museum presents the historical events of Gandhi's life as well as a spectrum of information technology visions inspired by Gandhian thought. The Web Page provides information on the various exhibits and video installations grant insight in the opening ceremony and the museum facilitites